Social well-being of the elderly in Hungary - Csinády, Adriána; Szemán-Nagy, Anita; Farkas, Réka; Almássy, Zsuzsanna (Magyar Gerontológia, 2022)
In our study, we intended to identify the components of social well-being in the elderly. An examination of the intrapsychic and the interpersonal aspect also played a role in our research. A number of areas were measured by a questionnaire, such as traits, social well-being, the amount of exercise and the range of daily activities.